Evaluating Inter- and Intraobserver Agreement on Pectus Carinatum Severity and Treatment Outcomes: A Comparison of Subjective and Objective Assessment Methods - van Braak, Hendrik; de Beer, Sjoerd A.; Zwaveling, Sander; Oomen, Matthijs W. N.; van Heurn, L W. Ernest; de Jong, Justin R. (European Journal of Pediatric Surgery, 2024)
Background Visual examination is crucial for assessing pectus carinatum (PC) severity and treatment results. This cross-sectional study evaluates the inter- and intraobserver agreement of PC deformities before and after treatment.Methods Observers examined medical photographs of patients before and after treatment. Primary outcome was inter- and intraobserver agreement on esthetic results after treatment. Secondary outcomes included inter- and intraobserver agreement on severity and symmetry before treatment, differences in esthetic results after Ravitch surgery and dynamic compression bracing (DCS bracing), and the impact of scars, age, and treatment duration on esthetic results.Results Medical photographs of 201 patients (aged 4–18) were evaluated by five surgeons and five peers. Surgeons and peers demonstrated inadequate (κ < 0.61) interobserver agreement on esthetic results (κ = 0.26, κ = 0.22), severity of PC (κ = 0.43, κ = 0.38), and symmetry (κ = 0.37, surgeons only). Agreement between surgeons and peers on esthetic results (κ = 0.37) and severity before treatment (κ = 0.54) was similarly inadequate. Surgeons and peers demonstrated inadequate intraobserver agreement on esthetic results (κ = 0.49, κ = 0.34), severity of PC (κ = 0.54, κ = 0.48), and symmetry (κ = 0.60, surgeons only). Deformities treated with Ravitch surgery were perceived as more severe but yielded better results. Peers, unlike surgeons, viewed scars as negatively impacting results. No relationship was found between results after treatment and treatment duration (p = 0.682, p = .062) or age (p = 0.205, p = .527).Conclusions Subjective assessment of PC severity and esthetic results is inconsistent. Three-dimensional scanning could help standardize treatment completion and aid patients and surgeons in determining treatment completion. The psychosocial effects of scars should be addressed when discussing treatment options.
Keywords: pectus carinatum; intraobserver agreement; interobserver agreement; DCS bracing; Ravitch surgery